Startups in South Africa, Barriers to Growth and Opportunity through Unconventional International Structures - Kelly, Timothy Peter (Department of Commercial Law, 2023)
The topics dealt with in this paper are in the context of and applicable to early-stage technology companies (“startups”). This paper discusses what a startup is and the relevance of startups in South Africa. It will further consider the challenges faced by startups in South Africa, particularly the lack of access to funding and market opportunity. It will further discuss the opportunities that are available for startups offshore, specifically with regard to funding, market growth and opportunity. Following on from this, it will delve into the different international structures available to startups, which include the loop structure and the mirror structure. The paper will go on to discuss the conventional loop structure, which entails an offshore holding company with South African shareholders, which owns a South African entity – as well as the current legislation and restrictions in place which regulate the loop structure, also taking into account market opinion and the recent legislative development of the loop structure. Thereafter and forming the body of the paper, it will discuss the interplay between transfer pricing, tax residency and intellectual property in the context of setting up a mirror structure. These elements considered together deal with the factors which need to be taken into account by a startup when immigrating the headquarters of a company to an offshore jurisdiction in a tax efficient manner, and importantly dealing with the evolution of intellectual property (being the core asset of value relevant to an early-stage technology company) in the offshore jurisdiction. The elements to be considered in this regard include the establishment of the place of effective management of a company, what a controlled foreign company is, understanding foreign business establishment, the pre-requisites to dealing with intellectual property from a transfer pricing perspective and how these factors can be re-engineered to ensure that newly developed intellectual property is created offshore. Finally, this paper will consider the South African Venture Capital Association's perspective on the current regulations regarding the loop structure, and why the mirror structure is considered to be a safer alternative for technology start-ups who are looking to move offshore.